ACTOS Y GRADOS DE LA UNIVERSIDAD DE ALCALA (1544-1562) - RAMIS BARCELO, RAFAEL; RAMIS SERRA, PEDRO (DYKINSON, 2024)
This book, authored by Rafael Ramis Barceló and Pedro Ramis Serra, provides a detailed examination of the University of Alcalá during the years 1544-1562. It is part of a series that delves into the history of universities, particularly focusing on the academic institutions' development from the Late Middle Ages. The work systematically presents historical records of academic acts and degrees, highlighting key figures and events associated with the University of Alcalá during an era significant for its alignment with the Council of Trent. The book is aimed at scholars interested in 16th-century academic history and offers exhaustive data on professors, graduates, and the academic framework of the time, contributing valuable insights into the intellectual climate of early modern Spain.